Analysis of the Impact of Free Cash Flow, Agency Cost, and Earning Management against Share Return - Virginia Septrinova; Edi Edi (Universitas Internasional Batam, 2021)
The purpose of this research is to analyze free cash flow, agency cost, and earning management influence against share return. The research object is firm that listing in Indonesia stock exchange in period 2015 to 2019, by using purposive sampling method. The results of this study, free cash flow and agency cost generated insignificant effect result on share return, and earning management is the independent variable that generated significant positive effect result on share return. This research will provide empirical data that good corporate governance doesn’t have significant effect toward share return.